Effects of the innovation climate on turnover intention in the Australian public service - Demircioglu, Mehmet Akif; Berman, Evan (American Review of Public Administration)
Employee turnover is an important concern for many public organizations, and research is increasingly seeking to understand the factors associated with this phenomenon. This article analyzes the effect of innovation climate on turnover intention (TI); it theorizes that an innovation climate encourages employee participation and creativity, thereby making jobs more interesting and reducing TI. Using data from the Australian Public Service (APS), an organization concerned with innovation and reducing TI, this study finds that innovation climate reduces three types of TIs to another agency, to the private sector, and to retire. This result is robust across a broad range of occupations and types of employees (frontline, senior, and management), and we have controlled for measures that are frequently studied, such as job satisfaction and salary satisfaction. This article suggests that policy makers should remove barriers to innovation and encourage activities and supervisory practices that make jobs more interesting$1 (Band, thus, the innovation climate stronger$1 (Bas these actions may reduce employee turnover.- Reproduced.s
Keywords: Public sector - Australia; Innovation